2009
DOI: 10.3382/ps.2009-00015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of supplemental dietary poultry fat on the performance of commercial layers inoculated before or at the onset of lay with F-strain Mycoplasma gallisepticum

Abstract: The effects of F-strain Mycoplasma gallisepticum (FMG) inoculation and 1.5% supplemental dietary poultry fat (PF) on the performance of commercial layers between 20 and 58 wk of age were investigated. Sham and FMG inoculations were administered at 12 (before lay) and 22 (early in lay) wk and dietary treatments (basal control diets and basal control diets with 1.5% supplemental PF) were initiated at 20 wk of age. Mortality at wk 47 and 53 was greatest in birds inoculated with FMG at 22 wk. Feed consumption from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 26 publications
2
26
1
Order By: Relevance
“…Although Peebles et al [50] observed no effect of HpFMG eye drop inoculations at either 12 or 22 wk of age on subsequent hen mortality, in these same birds, Peebles et al [51] reported that the inoculation of HpFMG (across the 12 and 22 wk of age inoculation periods) decreased EP on wk 22 and 23 by an average of 5.4% (% of hen-day EP), but increased EP on wk 45 by 3.4% (% of henday EP) without affecting total EP, egg weight, eggshell quality, relative weights of the yolk and albumen, or yolk moisture and lipid concentrations. In other work, Park et al [52] noted in commercial laying hens that feed consumption from 20 to 23 wk and from 52 to 55 wk of age was greater, but that percentage EP on wk 27 and 58 was higher and that on wk 47 was lower in response to the inoculation of HpFMG at either 12 or 22 wk of age. Nevertheless, total EP between 22 and 58 wk of age was highest in hens that were inoculated with HpFMG at 22 wk of age.…”
Section: Description Of Problemmentioning
confidence: 86%
See 4 more Smart Citations
“…Although Peebles et al [50] observed no effect of HpFMG eye drop inoculations at either 12 or 22 wk of age on subsequent hen mortality, in these same birds, Peebles et al [51] reported that the inoculation of HpFMG (across the 12 and 22 wk of age inoculation periods) decreased EP on wk 22 and 23 by an average of 5.4% (% of hen-day EP), but increased EP on wk 45 by 3.4% (% of henday EP) without affecting total EP, egg weight, eggshell quality, relative weights of the yolk and albumen, or yolk moisture and lipid concentrations. In other work, Park et al [52] noted in commercial laying hens that feed consumption from 20 to 23 wk and from 52 to 55 wk of age was greater, but that percentage EP on wk 27 and 58 was higher and that on wk 47 was lower in response to the inoculation of HpFMG at either 12 or 22 wk of age. Nevertheless, total EP between 22 and 58 wk of age was highest in hens that were inoculated with HpFMG at 22 wk of age.…”
Section: Description Of Problemmentioning
confidence: 86%
“…However, the benefit of the supplemental PF on feed consumption was lost if the birds had been inoculated with HpFMG at 12 wk of age. Park et al [52] further showed that this same type and timing of diet supplementation reduced feed consumption throughout lay in birds that experienced an inoculation procedure (sham or HpFMG) at 12 wk of age. Although Park et al [52] reported that the 1.50% supplemental PF did not augment the eggshell quality of the hens subjected to inoculation (sham or HpFMG), in a report in which the same birds were used, Park et al [53] found that the use of 1.50% supplemental PF increased percentage of yolk weight and the yolk:albumen ratio across hen age, inoculation type (sham or HpFMG), and inoculation age (12 or 22 wk of age), and decreased yolk concentrations of palmitic and oleic acid while increasing those of linoleic acid at 58 wk of age.…”
Section: Pfmentioning
confidence: 95%
See 3 more Smart Citations